Usefulness of a set of radiocarbon dates for the reconstruction of changes in the environment of the Vistulian decline in Central Poland: https://doi.org/10.26485/AGL/2017/106/9 - Dzieduszyńska, Danuta (Acta Geographica Lodziensia, 2018)
The article presents the use of a set of radiocarbon dates for the identification of the pace of changes in the natural palaeoenvironment of the Łódź region (Central Poland). Based on 175 dates covering a time interval between 18–11.5 ka cal BP, the probability density function was constructed, the fluctuations of which correspond to the chronology of morphogenetic processes. Three stages in the Late Vistulian history of the Łódź region were distinguished and the age of their boundaries was established. The onset of postglacial warming at ca. 18 ka cal BP has been confirmed. The proposed chronostratigraphic division was compared with independent environmental data – stratigraphy based on Greenland ice cores and interdisciplinary studies of lake sediments. The correlation of records indicates the usefulness of the method as a supplementary tool in palaeogeographical reconstructions.